A Unique Factor XIII Mutation in Southeastern Iran with an Unexpectedly High Prevalence: Khash Factor XIII - Dorgalaleh, Akbar; Tabibian, Shadi; Shams, Mahmood; Majid, Golbahar; Naderi, Majid; Casini, Alessandro; Tavasoli, Behnaz; Gheidishiran, Maryam; Daneshi, Maryam; Safa, Majid (Seminars in Thrombosis and Hemostasis, 2019)
Congenital factor XIII (FXIII) deficiency is an extremely rare hemorrhagic disorder characterized by a deficiency of FXIII and associated with a high rate of morbidity and mortality. The disorder is more frequent in Iran, especially in Khash, a city in the southeast of the country. As identified in the current report, the prevalence of FXIII deficiency in this city is 1 homozygote per approximately 500 population (which is ∼4,000 times higher than the worldwide prevalence) with 3.5% heterozygotes. The disorder is accompanied by a high rate of mortality in rural areas of Khash, given an averaged observed rate of approximately three deaths per each family with FXIII deficiency, mostly due to late-diagnosis and/or misdiagnosis, and fetal consequences of both umbilical cord and central nervous system bleeding. Almost all patients with FXIII deficiency in the southeast Iran have a unique mutation in F13A gene (Trp187Arg), which leads to a severe FXIII deficiency. This mutation is used for pre-marriage and prenatal diagnosis, as well as for carrier detection and diagnostic confirmation. Fibrogammin P has been used worldwide for about one decade, along with different therapeutic regimens for prophylaxis treatment, major and minor surgeries, and successful delivery. Due to the rapid increase in the number of patients identified to have congenital FXIII deficiency, and the high rate of related morbidity and mortality, a comprehensive regional preventive program is necessary to prevent further expansion of this condition and decrease the burden on the health care system. The area of Khash city provides novel insights into severe FXIII deficiency due to its high prevalence in this region. This report also provides a review of FXIII deficiency, its diagnosis, prevalence, molecular basis, clinical manifestations, management, and treatment, with a particular focus on Iran, representing a hotspot for this disorder.
Keywords: factor XIII deficiency; Khash city; southeastern Iran; morbidity; mortality